On the basis of sex: a liberal feminist analysis of women’s struggle for education - Yashinta, Friska Oktaviani; Nurhayati, Sulasih (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
This study delves into the portrayal of women's struggles for education as depicted in the Hollywood film “On the Basis of Sex.” It seeks to address the pervasive influence of patriarchal dominance that impedes women's educational rights. The narrative is primarily framed around the life experiences of the film's central figure, Ruth Bader Ginsburg, who contends with male counterparts in her quest for admission to prestigious law school programs in the United States. Simultaneously, feminists advocate for education as a cornerstone for women's empowerment and gender equality. It empowers women to become agents of change, thereby emphasising their equal rights to shape a better world. The research adopts a qualitative approach, collecting both primary and secondary data, and employs liberal feminist critical theory for data analysis. Key findings reveal the disadvantaged state of American women in the late 1950s, marked by limited educational access. Despite these obstacles, women, exemplified by Ginsburg, displayed unwavering determination and unity in their pursuit of improved educational opportunities, subsequently expanding their presence in the legal profession and public employment. Ginsburg’s remarkable journey serves as an enduring symbol of resilience and inspiration for others, reaffirming the notion that education is a universal right transcending gender barrier.